Analysis of Effective Factors on Employment Rate in Provinces of Iran: A Spatial Panel Data Approach - Razieh Kardgar; Nooraddin Sharify; Zahra Mila Elmi (مدلسازی اقتصادسنجی, 2023)
The formation of the spatial employment pattern in a region is influenced by various geographical, economic, social, and climatic characteristics. In this regard, this paper analyses the effective factors on employment rates in 31 Provinces of Iran over five years (2011-2016). For this purpose, the spatial autocorrelation with direct and indirect effects (spatial spillover) of Factors on employment rate in provinces of iran has been estimated using the panel data and spatial econometrics method (Spatial Durbin model). The results of spatial estimation showed that there is spatial autocorrelation in the provincial employment rate. Other results indicate that the GDP of the provinces has a significant positive direct and spatial spillover effect on the employment rate. On the other hand, energy intensity has a significant negative direct and spatial spillover on the employment rate. The amount of rainfall does not directly affect the employment rate. The study finds an inverse U-shaped relationship between direct and indirect effects of net migration, population density variables, and the employment rate. Therefore, by increasing in immigration and population density, the employment rate increases in the studied provinces and neighboring provinces, and it decreases after crossing the threshold.